2018
DOI: 10.3390/nu10111724
|View full text |Cite
|
Sign up to set email alerts
|

Spices and Atherosclerosis

Abstract: Cardiovascular disease is one of the leading causes of death and disability in the world. Atherosclerosis, characterized by lipid accumulation and chronic inflammation in the vessel wall, is the main feature of cardiovascular disease. Although the amounts of fruits and vegetables present in the diets vary by country, diets, worldwide, contain large amounts of spices; this may have positive or negative effects on the initiation and development of atherosclerosis. In this review, we focused on the potential prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 103 publications
0
33
0
1
Order By: Relevance
“…In contrast, the western-style diet is characterized by a high intake of salt and sugar, and it is considered rather spice-free. However, the popularity of oriental cuisine and a growing preference for ethnic or spicy food raised the consumption of spices in Europe and North America [2,3]. Data indicate that the EU market is the largest market for herbs and spices in the world and the leading consumers (among EU citizens) are Germans, British, Romanians and Hungarians [4].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, the western-style diet is characterized by a high intake of salt and sugar, and it is considered rather spice-free. However, the popularity of oriental cuisine and a growing preference for ethnic or spicy food raised the consumption of spices in Europe and North America [2,3]. Data indicate that the EU market is the largest market for herbs and spices in the world and the leading consumers (among EU citizens) are Germans, British, Romanians and Hungarians [4].…”
Section: Introductionmentioning
confidence: 99%
“…Spices typical for Indian cuisine are turmeric, saffron, cardamom, cinnamon, cloves, garlic, peppers, cumin and coriander. Mediterranean-style cuisine is famous for parsley, oregano, basil, thyme, dill, fennel, marjoram, rosemary, bay leaf, lavender, sage, savory, cumin and coriander [3,7]. In China, the most popular condiments include peppers, peppercorns, ginger, fennel, cloves, star anise and cinnamon, whereas Italian and Greek cuisine is rich in basil, garlic and oregano.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent study, a number of spices, such as pepper, ginger, garlic, onion have been found to act against atherosclerosis. 15 Wu et al suggest that andrographolide (a bitter diterpene lactone) ameliorates atherosclerosis by suppressing pro-inflammation and Reactive Oxygen Species (ROS) generation pathways. 16 Both, NSO and PHY are evident to possess ROS scavenging and antiinflammatory effects.…”
Section: Discussionmentioning
confidence: 99%
“…Garlic has been used since ancient times to suppress the growth of bacteria, fungi and viruses (21). It has been demonstrated that garlic extract and its components attenuate atherosclerosis (22) and hypertension (23), and exert immunomodulatory and anti-tumor effects (24). It has also been found that the aqueous extract of garlic (21,25) and its components, allicin (26) and diallyl sulfide (27), inhibit the growth of the periodontal pathogens, P. gingivalis, Aggregatibacter actinomycetemcomitans and Fusobacterium nucleatum in vitro.…”
Section: Evidence Of the Inhibitory Effect Of Various Naturally Occurmentioning
confidence: 99%